(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2021)
This work, which focuses on the three functions of university, describes the experience of the University Subject Education and Nutritional Food Communication of the course on Nutrition at Food Science School of the National University of Entre Ríos (UNER). The aim was to offer students the opportunity to work in scenarios where learning and teaching are bidirectional, which allows them to get involved in decision-making in the research process and in solving real problems in the community. Research and extension practices were integrated in the curriculum. Within this framework, the Participatory Action Research (PAR) project was generated in 2018: “Conceptions and educational and communicational knowledge about community practices of health promotion and disease prevention of healthcare professionals and teams of the city of Gualeguaychú, aimed at young people and adults”, whose lines of action are critical extension actions.